TRIM3 attenuates cytokine storm caused by Dabie bandavirus via promoting Toll-like receptor 3 degradation - Jin, Ke; Dai, Yan; Ouyang, Ke; Huang, Huaying; Jiang, Zhengyi; Yang, Zhan; Zhou, Tingting; Lin, Hong; Wang, Chunhui; Wang, Chunyan; Sun, Xuewei; Lu, Dafeng; et al. (Frontiers in Microbiology, 2023)
Background: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease that was caused by Dabie bandavirus (DBV), and it has become a global public health threat. Cytokine storm is considered to be an important pathogenesis of critical SFTS. Tripartite motifcontaining 3 (TRIM3), as a member of TRIM protein, may contribute to the regulation of immune response and inflammatory response after viral infection. However, whether TRIM3 plays a major role in the pathogenesis of SFTS has not yet been investigated.Methods: TRIM3 mRNA levels were detected in PBMCs between 29 SFTS patients and 29 healthy controls by qRT-PCR. We established the pathogenic IFNAR -/-SFTS mice model successfully by inoculating subcutaneously with DBV and tested the expression levels of TRIM3 mRNA and protein by qRT-PCR and immunofluorescence in the livers, spleens, lungs, and kidneys. TRIM3 OE THP-1 cells and peritoneal macrophages extracted from TRIM3 -/-mice were infected with DBV. The effect of TRIM3 on cytokines was detected by qRT-PCR and ELISA. Then we examined Toll-like receptor 3 (TLR3) and protein phosphorylation in MAPK pathway after DBV infection using Western blot. Flow cytometry was utilised to verify TLR3 expression on peripheral blood monocytes in SFTS patients. We further explored the interaction between TRIM3 and TLR3 using CO-IP and Western blot.Results: Compared to healthy controls, TRIM3 mRNA expression in PBMCs is decreased in SFTS patients, especially in severe cases. TRIM3 mRNA and protein synchronously reduced in the livers, spleens, lungs, and kidneys tissues of IFNAR -/-SFTS mice model. In DBV-infected cell model, TRIM3 overexpression can inhibit the DBV-induced release of IL-1β, IL-6 and TNF-α, expression of TLR3 and protein phosphorylation in the MAPK pathway, which plays an anti-inflammatory role, while TRIM3 deficiency exacerbates the pro-inflammatory effects. We further found that TRIM3 can promote TLR3 degradation through K48-linked ubiquitination.TRIM3 can inhibit the production of cytokines by regulating the degradation of TLR3 through K48-linked ubiquitination, which can be a therapeutic target for improving prognosis of SFTS.